Dendrogeomorphology as a tool to depict hydrogeomorphic processes in the tropics - Quesada Román, Adolfo (2023)
Climatic and anthropogenic changes cause the deprivation of distinct ecosystems in Costa Rica, transforming climatic, ecological, and geomorphic conditions. The high tropical biodiversity of Costa Rica and the tropics is suitable to improve the understanding of hydrogeomorphic process dynamics and to produce baseline data on past disasters in scarce-data regions. The principal motivation to connect natural hazards and dendrochronology on tropics is the desire to create methods that can reduce its exposure and vulnerability. The principal research aim of this study is to give reference data that can improve the understanding of hydrogeomorphic processes and to explore the potential of tropical trees in dendrochronological applications. This paper combines remote sensing, meteorological assessments, and dendrochronology analyses, hydraulic modelling, and risk assessments. This innovative research describes the reduced understanding in treering analysis in Costa Rica related with past disasters and their linkage to climate. This study will likely contribute to the implementation of new methodologies in disaster risk research, and it will promote future adaptation strategies in the most biodiverse region of the world.